Effect of Pb Addition on the Solidification Microstructure and Precipitation Behavior of Al–10Si–0.4Mg–0.4Cu Alloy Fa bricated by High-Pressure Die Casting - Park, Seonghyun; Jeon, Jungmin; Lee, Seok-Jae; Jung, Jae-Gil (Archives of Metallurgy and Materials, 2026)
We studied the effect of Pb addition on the solidification microstructure and precipitation behavior of an Al–10Si–0.4Mg–0.4Cu alloy fabricated by high-pressure die casting (HPDC) using thermodynamic calculations and scanning and transmission electron microscopy analyses. Pb addition induced the formation of Pb phase along the grain boundaries of Al and Al/Si eutectic during solidification. Aging at 160°C induced the formation of spherical or needle-like Si nanoprecipitates and embedded β'' nanoprecipitates in both Pb-free and Pb-added alloys. Strong Pb segregation was observed at the interface of Si nanoprecipitates, which inhibits precipitate growth during aging. Si refinement due to Pb segregation and newly formed Pb nanoprecipitates slightly enhanced the age hardening reaction after T5 heat treatment. This study can provide insights into the strategies to control the microstructure of recycled HPDC Al alloys containing Pb.